Human behavior and the social environment. Macro level. Groups, communities, and organizations. 2nd ed. - van Wormer, Katherine; Besthorn, Fred H. (New York, 2011)
"A timely revision in this global age, Human Behavior and the Social Environment, Macro Level develops a sophisticated and original view of the cultural, global, spiritual, and natural worlds that people inhabit, and the impact of these worlds on human behavior. Its major new theme, sustainability, emerges as a key characteristic of contemporary practice. What is sustainable social work? What are the characteristics of a sustainable community? How is the present exploitation of environmental resources unsustainable for future generations? Following the greatest economic upheaval since the Great Depression, how can we envision a sustainable economy that will benefit all the people, not only the wealthy few? Human behavior results from biological, psychological, socio-economic, and cultural forces, but the mental health field has placed the most emphasis on intrapsychic factors to the near exclusion of socio-economic and cultural considerations. This significant collaboration seeks to correct this omission by helping students recognize patterns in the family, culture, and value systems in order to create safe and sustainable environments for their future clients. The emphasis on sustainable and unsustainable social welfare programs is geared to helping readers engage in advocacy for social justice."